2013
DOI: 10.1148/radiol.12121681
|View full text |Cite
|
Sign up to set email alerts
|

Glenoid Bone Loss: Assessment with MR Imaging

Abstract: MR imaging assessment of glenoid bone loss, particularly with use of glenoid width, is almost as accurate as CT assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 24 publications
2
57
0
3
Order By: Relevance
“…In these cases, the loss of bone anteriorly coupled with the remaining non-circular margin resulted in incorrect estimation of the native bone contour (Figure 6). Other authors have noted similar limitations when using the best-fit circle method [18, 25]. However, we found that measuring glenoid diameters using IR-UTE-Cones and 2D CT were very accurate when compared to our reference standard of 3D CT and reliable between raters.…”
Section: Discussionsupporting
confidence: 65%
“…In these cases, the loss of bone anteriorly coupled with the remaining non-circular margin resulted in incorrect estimation of the native bone contour (Figure 6). Other authors have noted similar limitations when using the best-fit circle method [18, 25]. However, we found that measuring glenoid diameters using IR-UTE-Cones and 2D CT were very accurate when compared to our reference standard of 3D CT and reliable between raters.…”
Section: Discussionsupporting
confidence: 65%
“…Osseous subluxation injury and morphologic changes due to osteoarthritis were evaluated. Bankart lesions were evaluated for width and percentage width loss relative to a circle fit to the inferior glenoid periphery (Fig E1 [online]) (14,15). Best-fit circle diameter was used as an additional measure for assessing agreement.…”
Section: Methodsmentioning
confidence: 99%
“…A quantification method for anterior Bankart lesions using three-dimensional CT was described by Chuang et al and accurately predicted the need for bonegrafting in patients with osseous Bankart lesions 46 . In a head-to-head comparison between CT and MRI, the correlation between CT and arthroscopy was slightly better than that between MRI and arthroscopy for quantifying anterior glenoid bone loss 47 . However, to our knowledge, there has been no definitive work using the same radiographic methods to specifically assess and quantify posterior glenoid bone loss.…”
Section: Reverse Soft-tissue or Osseous Bankart Reverse Hill-sachs mentioning
confidence: 83%